Material needs security and cardiovascular risk factors in rural South Africa - Rebekah J. Walker; Caitlin Magro; Rabia Amjad; Laura C. Hawks; Sandra Iregbu; Leonard E. Egede (BMC, 2024)
Abstract Background The prevalence of cardiovascular disease is burgeoning in low- and middle-income countries (LMICs). In sub-Saharan Africa, the prevalence of cardiovascular risk factors is increasing, though rates of CVD diagnosis and management remain low. Awareness of the influence of social determinants of health (SDOH) on cardiovascular outcomes is growing, however, most work focuses on high-income countries. Material needs security is a measure of SDOH that may be particularly relevant for LMICs. This study investigated the relationship between material needs security and cardiovascular risk in older adults living in South Africa. Methods The analysis included 5059 respondents age ≥ 40 in the Health and Aging in Africa survey, an observational cohort study administered in 2014 in Mpumalanga Province, South Africa. Linear regression models tested the association between material needs and eight cardiovascular risk factors (waist-to-hip ratio, body mass index, blood pressure, glucose, cholesterol, LDL, and triglycerides). Adjusted linear regression models controlled for sociodemographic confounders. Results There were significant adjusted associations found between increased material needs security and four cardiovascular risk factors, including waist-to-hip ratio (β = 0.001; 95% CI [0.00002,0.002]), BMI (β = 0.19; 95%CI=[0.14,0.24]), glucose (β = 0.46; 95%CI=[0.02,0.90]), and triglycerides (β = 0.26; 95%CI=[0.02,0.49]). Conclusion Increased material needs security was associated with significantly increased cardiovascular risk in older adults in rural South Africa. These findings can inform the approach to treatment and management of cardiovascular disease in South Africa and similar LMICs. Future investigations should evaluate the implementation and efficacy of interventions that recognize the role of material needs security in cardiovascular risk.